Catalytic oxidative chemical treatment for the removal of elemental mercury on carbon steel (SAE J429) surface - Khairuddin, Farah Ilyana (2012)
In this study, mercury contaminated carbon steels was prepared using droplet and physisorption methods. Various oxidants were applied to oxidize the mercury element and the oxidized mercury and the iron leaching were analyzed using Atomic Absorption Spectrometer (AAS) for data collections. The effect of oxidant system of KI/I2, peracetic acid, different conditions of experiment namely heating, stirring, left at room temperature, the presence of catalysts and the addition of imidazoline based corrosion inhibitor were investigated. The experiment revealed the oxidant system of 1H2O2:1CH3COOH (peracetic acid) ratio as the best to remove 96.43% physisorbed Hg and 96% droplet Hg from carbon steel surfaces under ambient temperature and soaking for 5 hours. The total iron leached detected under the optimum condition from used carbon steel contaminated with physisorp Hg and droplet Hg were 21.45 ppm and 22.98 ppm respectively. Interestingly, the presence of Ru/Mn (25:75)/Al2O3 catalyst calcined at 1000°C with peracetic acid as oxidant could further remove 99% of Hg for CS-physisorbed-Hg and 98.71% for CS-droplet-Hg resulting in 19.71 ppm and 19.62 ppm respectively iron leached in 3 hours. FESEM illustrated the catalyst surface is covered with small and dispersed particles with undefined shape. From FESEMEDX analysis, Mn species were detected in all the catalysts tested. The X-Ray Diffraction (XRD) analysis revealed that the catalyst is crystalline and Mn species is believed to be the active species for the catalysts. Nitrogen Gas Adsorption (NA) analysis showed that both fresh and spent catalysts are of mesoporous material with Type IV isotherm and type H3 hysteresis loop.